منهج الكليني في كتاب الحجة : دراسة نقدية حديثية - رحمن، محمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
It is known that the Twelve Imami Shi'ites have their own sources, just like the Sunnis (Ahl al-sunnah wa al-Jamaa'h), and one prominent source is the Book of Hujjah (Kitab al-Hujjah), the fourth book of Kulayni's Ushul Kafi which is widely considered as the finest and most authentic book of Hadith of the Shi'ites. Thus, there is no doubt that the presentation of Kulayni's methodology and approach is very important for being one of the prime Hadith sources they have. This book, therefore, is significant in explaining the doctrine of the Twelve Imami Shi'ites, and in the understanding of their faith founded on the consideration of the Hadith in it. This study aims to identify Kulaynī's personality and his book Hujjah, and the approach and methodology he used, with access to his classification of narrators and narrations, and to study them in the light of the Hadith Criticism. It uses the inductive, analytic, and critical methods. Based on this study, the researcher derives valuable results as follows: Kulayni and his works have attained a significant designation among the Twelve Imami Shi'ites followers. He writes in a typical, distinctive style which differs from the other Shi'ites Hadith scholars. Kulayni extensively drew from those who are considered by the Shi'ites scholars of Rijal as liars, extremist narrators and accursed transmitters. Although his narrations often end with the infallible Imams, yet there is no single narration as reported by the companions